O-021 Hospitalization costs for endovascular and surgical treatment of unruptured cerebral aneurysms in the USA are substantially higher than medicare payments. (12th July 2011) - Brinjikji, W; Kallmes, D; Lanzino, G; Cloft, H
Abstract : Background and Purpose: Endovascular and surgical options are both available for the treatment of unruptured cerebral aneurysms. Knowledge of the costs for hospitalization of these patients is important to understanding economic impact of these patients on hospitals. Methods: Using the National Inpatient Sample, hospitalizations for clipping and coiling of unruptured cerebral aneurysms from 2001 to 2008 were identified by cross-matching ICD-9 codes for diagnosis of unruptured aneurysm with procedure codes for clipping or coiling of cerebral aneurysms, and excluding all patients with diagnosis of subarachnoid hemorrhage and intracerebral hemorrhage. Hospital costs for 2008 were correlated with age, gender, and discharge status, and compared to Medicare payments. Results: Costs of both clipping and coiling have increased from 2001 to 2008. The median 2008 hospital costs were US23 574 (IQR 18233–29941) for clipping and US25 734 (IQR 17436–35846) for coiling without complication, which were higher than the average Medicare payment of US12 599. The median hospital costs were US36 188 (IQR 21831–55308) for clipping and US40 502 (IQR 24289–50108) for coiling treatments complicated by major morbidity, and US68 165 (IQR 32972–100211) for clipping and US56 020 (IQR 00000–00000) for coiling treatments complicated by mortality, which were higher than the average Medicare payments for patients with major complications and comorbidities of US22 946. In multivariate analysis, female gender was associated with higher costs for coiling (p=0.02), and poor discharge status was associated with higher costs for both clipping (p<0.001) and coiling (p<0.001). Conclusions: Hospitalization costs for patients undergoing clipping and coiling of unruptured cerebral aneurysms are substantially higher than Medicare payments.